Hexagon fraud: Detection of fraudulent financial reporting in state-owned enterprises Indonesia - Achmad, Tarmizi; Ghozali, Imam; Pamungkas, Imang Dapit (Economies, 2022)
This study aims to detect fraudulent financial reporting using hexagon fraud analysis, including seven factors: financial stability, external pressures, ineffective monitoring, auditor changes, change in director, arrogance, and collusion. The subject of this research is a public company consolidated audit report of state-owned enterprises. The existence of conflicting results, the phenomenon of fraudulent financial reporting, and limited research using the hexagon of fraud theory prompted this research to examine the factors that influence fraudulent financial reporting. The sample was selected using a sampling technique, with the criteria of state-owned enterprises listed on the Indonesia Stock Exchange in 2016-2020. The method used is quantitative, and the analytical method used is logistic regression analysis. The sampling technique used was purposeful sampling, so the number of samples was 125. The results of this study indicate that financial stability and external pressures have a positive effect on fraudulent financial reporting. However, ineffective monitoring, auditor changes, change in director, arrogance, and collusion do not affect fraudulent financial reporting.